Estimation and optimization of maximum deviations in dynamical control system under complexly shaped disturbances - Makarov, N. N.; Semashkin, V. E. (Journal of computer & systems sciences international, 2012)
The game problem of designing dynamical systems that are optimal with respect to extreme deviations subject to external actions is solved. The maximum (over time) of the absolute value of the function characterizing the quality of motion is used as the measure of deviation. A method for describing the set of possible external actions as a set of outputs of an additional dynamic block—a reference input generator (RIG) is proposed. The chief application domain of the results is the design of servomechanisms with the minimal extreme tracking error deviation. An example of designing a hydraulic servo drive is discussed.